Genetic diversity in rice (Oryza sativa) and estimation of outcrossing rate using morphological markers - Bah, Saidu (University of the Free State, 2015)
Rice is an important food crop with two domesticated species namely Oryza glaberrima Steud. also known as African rice and O. sativa L. also known as Asian rice. Rice is a self-pollinating plant that shows some level of outcrossing under field conditions. Understanding the levels of gene flow is important for managing the conservation and maintenance of germplasm for gene banks and plant breeding programmes. It is equally important for the production of quality rice seed. There is also the concern of gene flow between genetically modified rice and other rice species; wild relatives and weedy (red) rice. This study used agro-morphological and microsatellite markers to evaluate the diversity in a collection of 36 accessions consisting of intraspecific (O. sativa and O. glaberrima) and interspecific (O. sativa x O. glaberrima) hybrid genotypes. The Shannon-Weaver diversity index was low measured by agro-morphological markers. The highest level of diversity was detected in the Indica accessions and the lowest diversity in the O. glaberrima accessions. Japonica accessions had brown or green apiculus and were awnless. O. glaberrima and landrace accessions had purple apiculus and some were awned. The Japonica group comprised mostly of improved varieties with a white pericarp whilst O. glaberrima accessions and landraces had a red pericarp. Selected interspecific hybrids combined traits of O. sativa and O. glaberrima to varying degrees. Microsatellite markers showed a total of 321 alleles with an average of 11.9 alleles per locus and an average major allele frequency of 0.29 per locus. The average gene diversity value was 0.81 and polymorphism information content was 0.80 per locus. Diversity indices for interspecific hybrids were intermediate between O. sativa and O. glaberrima, but closer to the O. sativa Japonica group. Two populations were revealed which corresponded to the O. sativa Indica group and O. sativa Japonica group. Interspecific hybrid accessions were dispersed between the two groups. Microsatellite data detected higher diversity between accessions in comparison to agro-morphological data. There was correlation between the different matrices, indicating that they all reflected similar patterns in the structure of diversity of the collection. Agro-morphological markers of red kernel colour and leaf pilosity of the pollen donor was also used to estimate outcrossing rates in four genotypes of rice consisting of improved cultivars of O. sativa Japonica group (one accession) and interspecific hybrids (three accessions). The dominant markers of red kernel colour and leaf pilosity were effective in estimating outcrossing in rice. There was an average outcrossing rate of 0.7% + 0.51, with a potential outcrossing rate of 2.45% + 0.86. Outcrossing rates decreased with increase in distance. It ranged from 2.45% at 0.2 m from the donor to 0.05% at 25 m from the donor. Gene flow was influenced by type of genotype, the distance of recipient from the pollen donor and flowering synchronisation. The study suggests that natural outcrossing could be partly responsible for the appearance of non-uniform and off-type plants in rice fields in sub-Saharan Africa. The study recommends a minimum distance of 20 m between genotypes to minimise outcrossing to acceptable levels.

Rys is ‘n belangrike voedselgewas met twee aangeplante spesies naamlik Oryza glaberrima Steud., ook bekend as Afrika rys en O. sativa L., ook bekend as Asiese rys. Rys is ‘n selfbestuiwende gewas met ‘n persentasie kruisbestuiwing onder veldtoestande. ‘n Begrip van die hoeveelheid geenvloei is belangrik vir die bestuur en onderhoud van kiemplasma vir geenbanke en planteteelt programme. Dit is net so belangrik vir die produksie van kwaliteit ryssaad. Daar is ook kommer oor geenvloei tussen GM rys en ander rys spesies; wilde verwantes en onkruidagtige (rooi) rys. Hierdie studie het agro-morfologiese en mikrosatelliet merkers gebruik om diversiteit in ‘n versameling van 36 inskrywings bestaande uit intraspesifieke (O. sativa L. en O. glaberrima Steud.) en interspesifieke (O. sativa x O. glaberrima) rys genotipes te bepaal. Resultate van kwalitatiewe en kwantitatiewe eienskappe het verskille in diversiteit tussen die inskrywings getoon. Die waargenome diversiteit in O. glaberrima was laer as in O. sativa. Interspesifieke rys het intermediêre vlakke van diversiteit getoon. Die Shannon-Weaver diversiteitsindeks was laag gemeet aan agro-morfologiese merkers. Die hoogste diversiteitsvlak is gesien in die Indica inskrywings en die laagste diversiteit in die O. glaberrima inskrywings. Japonica inskrywings het bruin of groen aarpunte gehad en was baardloos. O. glaberrima en landrasinskrywings het pers aarpunte gehad, en sommige het baarde gehad. Die Japonica groep het meestal bestaan uit verbeterde variëteite met ‘n wit perikarp terwyl O. glaberrima inskrywings en landrasse ‘n rooi perikarp gehad het. Die interspesifieke basters het eienskappe van O. sativa en O. glaberrima gekombineer in verskillende grade. Mikrosatelliet merkers het ‘n total van 321 allele getoon met ‘n gemiddeld van 11.9 allele per lokus en ‘n gemiddelde major alleel frekwensie van 0.29 per lokus. Die gemiddelde geendiversiteitswaarde was 0.81 en die polimorfisme informasie inhoud was 0.80 per lokus. Diversiteitsindekse vir interspesifieke basters was intermediêr tussen O. sativa en O. glaberrima, maar nader aan die O. sativa Japonica groep. Twee populasies is aangetoon wat ooreenkom met die O. sativa Indica groep en O. sativa Japonica groep. Interspesifieke basterinskrywings was versprei tussen die twee groepe. Mikrosatelliet data het meer diversiteit tussen inskrywings uitgewys in vergelyking met agro-morfologiese data. Daar was korrelasie tussen die verskillende matrikse, wat gewys het dat hulle dieselfde patrone in die struktuur van die diversiteit van die versameling wys. Die agro-morfologiese merkers vir rooi saadkleur en blaarharigheid van die stuifmeelskenker is ook gebruik om die hoeveelheid kruisbestuiwing in vier genotipes van rys, bestaande uit verbeterde cultivars van O. sativa ssp. japonica (een inskrywing) en interspesifieke rys (drie inskrywings), te bepaal. Die dominante merkers van rooi saadkleur en blaarharigheid was effektief om die hoeveelheid uitkruising in die rys te bepaal. Daar was ‘n gemiddelde uitkruisingsvlak van 0.7% + 0.51, met ‘n potensiële uitkruisingsvlak van 2.45% + 0.86. Uitkruisingsvlakke het gewissel van 2.45% by 0.2 m van die donor tot 0.05% by 25 m van die donor. Geenvloei is beïnvloed deur die tipe genotipe, die afstand van die ontvanger vanaf die donor en blom sinkronisasie. Die kruisbestuiwingsvlakke was gewoonlik die hoogste by afstande naaste aan die skenker. Die studie het getoon dat natuurlike uitkruising gedeeltelik verantwoordelik is vir die voorkoms van nie-uniforme en af-tipe plante in ryslande in sub-Sahara Afrika.
Thesis (Ph.D. (Plant Sciences (Plant Breeding))--University of the Free State, 2015
Keywords: Agro-morphological; Diversity; Interspecific rice; Microsatellites; O. glaberrima; O. sativa; Outcrossing